Urogenital Chlamydia trachomatis in Gabon: an unrecognised epidemic. Issue 5 (October 1988) - Leclerc, A; Frost, E; Collet, M; Goeman, J; Bedjabaga, L
Abstract : Samples from 218 men with urethritis, 517 women with pelvic pain or pelvic pain and vaginal discharge, 218 women consulting for infertility, and 598 postpartal women were screened for Chlamydia trachomatis by culture and direct immunofluorescence. Chlamydiae were detected in 18% (39/218) of the men, 18% (45/252) of women with vaginal discharge, 14% (38/265) of those with pelvic pain, 10% (21/218) of infertile, and 10% (59/598) of postpartal women. A chlamydial prevalence of 18% (41) was observed in 229 postpartal women aged under 21, whereas only 5% (10) of 360 postpartal women over 21 had C trachomatis. In the other clinical groups, an age related decrease in prevalence was noted in women over 25. The direct immunofluorescence test correlated well with culture. The small difference in isolation between symptomatic and postpartal women indicates that women in this population do not seek medical attention for chlamydial infections and expose themselves to chlamydial salpingitis and infertility.